Hepatitis E Virus: A Cross‐Sectional Serological and Virological Study in Pigs and Humans at Zoonotic Risk within a High‐Density Pig Farming Area. Issue 5 (5th July 2016) - Caruso, C.; Peletto, S.; Rosamilia, A.; Modesto, P.; Chiavacci, L.; Sona, B.; Balsamelli, F.; Ghisetti, V.; Acutis, P. L.; Pezzoni, G.; Brocchi, E.; Vitale, N.; et al.
Summary: An increase in autochthonous hepatitis E virus (HEV) infections has been recorded in Italy suspected to be zoonotically transmitted from pigs; this study was carried out to determinate the seroprevalence and risk factors associated with hepatitis HEV exposition, both in swine and humans working in pig farms, located within a high‐density pig farming area in Piedmont region, north‐western Italy. The presence of viral RNA in human and swine samples was also evaluated, and phylogenetic analysis was performed on HEV‐positive samples. Forty‐two swine farms were sampled; 142 workers were enrolled in the study and classified into two groups: (i) 69 workers with occupational contact with swine (including veterinarians and farmers) recruited in the 42 sampled farms; (ii) 73 without occupational contact with swine. Forty‐one of 42 (97%) swine farms resulted positive to enzyme‐linked immunosorbent assay test for HEV antibodies (Abs). Overall seroprevalence in swine was 50% (441/879), with seropositivity rate higher in sows (333/469, 71%). HEV RNA in stool samples was detected in animals from 13 of 42 tested farms (31%), and a higher positivity resulted in weaners (40/246, 16.3%). Phylogenetic analysis classified all HEV isolates within genotype 3 (subtypes 3f, 3e, 3c). All humans were negative for HEV viral genome in blood. Five of 142 sera were positive for IgG anti‐HEV with an overall prevalence of 3.52% with no statistically significant differences in prevalence rates between workers at zoonotic risk and the control group (5.7% versus 1.3%). In contrast, a significant difference (OR 10.1) was observed within the subgroup including subjects exposed for short periods (veterinarians) compared with those who worked for long periods (farmers) suggesting a correlation between the time of exposure and the likelihood of HEV infection. Reporting HEV infection is not mandatory in Italy, but a constant epidemiological surveillance should be ensured to clarify the epidemiology of this disease.